Obesitas dengan Peningkatan Kadargula Darah Sewaktu pada Remaja di SMAN Palangka Raya - Natalansyah Natalansyah; Ayu Christiani Febriana; Supriandi Supriandi (POLITEKNIK KESEHATAN KEMENKES PALANGKA RAYA, 2019)
Obesity is a complex disorder of feeding and energy metabolism that is controlled by several specific biological factors. Obesity occurs because of an imbalance between energy intake and energy output (energy expenditures) so that the excess energy is stored in the form of fatty tissue. The excess of energy can be caused by high energy intake or low energy output. The design of this study was cross sectional. The number of research subjects of this study is about 42 peoples who have been measured the blood sugar levels at the time. The subjects of this study were aged 15-18 years old that has been taken with total sampling method. All subjects who have been qualified and have signed the consent sheet will be measured weight, height, body mass index, and blood sugar levels. Further data will be analyzed using SPSS program. The purpose of this study was to determine the relationship of Obesity with Increased Blood Sugar Levels of students in SMAN 2 Palangka Raya. The result showed that 21 subjects who were obese, 18 peoples showed an elevated blood sugar level and 3 peoples showed normal blood sugar levels. Based on Chi Square test, p value is about 0.020 with interpretation is smaller than α (0,05). Conclusion based on the results of this study can be concluded there is a significant relationship between Obesity with Increased Blood Sugar Levels.